Influence of Organizational Resources on Performance of Agencies Constituting the National Council on the Administration of Justice in Kenya - Mekolela, Agosta; Deya, Jared; Kariuki, Paul (European Journal of Business and Strategic Management, 2024)
Purpose: Strategy implementation drivers are elements that shape an organization's strategy and determine important success elements, long-term prosperity, and essential value propositions. The National Council on the Administration of Justice in Kenya comprises of state and non-state actors in the administration of justice. They play a role in establishing and maintaining a favorable environment for the economic, social, and political development of the country as envisaged in Kenya's Vision 2030. The agencies in the administration of justice have formulated strategic plans but despite the existence of strategic plans, they have been criticized for underperformance with the implementation of the strategic plans being marred with challenges which include; clogging up of the Justice system with petty offenses, systemic, structural and agency challenges, low rate of successful prosecution of serious offenses and justice system being skewed against the poor. The purpose of this study was to determine the influence of organizational resources on the performance of the agencies constituting the NCAJ. With a specific objective to establish the influence of tangible, intangible, and human resources on the performance of the agencies constituting NCAJ and to assess the moderating role of the regulatory environment on the relationship. Methodology: The study was anchored on resource-based theory. The study used a descriptive correlational survey research design and utilized both qualitative and quantitative data. The study's unit of analysis was the 36 institutions that comprise the NCAJ while the unit of observation was 231 drawn from the top and middle-level managers with a sample of 164 obtained using the Yamane formula. Primary data was collected by use of interviews and structured questionnaires administered by trained research assistants. Secondary data was collected from reports of NCAJ. A pilot study of 10% of the sample frame was conducted and those who participated in the pilot study were excluded from the final study. Cronbach's alpha and exploratory factor analysis were used to test for reliability and validity of the data collection instrument. Both descriptive and inferential statistics were used to analyze data with the help of the SPSS tool. Descriptive statistics was presented by use of measures of central tendency and measure of variability in tables while inferential statistics was presented by use of a regression model. Findings: The study found that tangible resources, intangible resources, and human resources have a significant and positive relationship with the performance of the agencies constituting the NCAJ. Thus, the study concluded that there is a strong significant positive relationship between organizational resources (r=.560 and p<0.05) and the performance of the agencies constituting the NCAJ. The study also found and concluded that Regulatory Environment has a moderating influence on the relationship between organizational resources and the performance of the agencies constituting the NCAJ (r=.241 and p<0.05). Unique Contribution to Theory, Practice and Policy: From the findings, the study recommended that NCAJ should enhance their tangible, intangible, and human resources as this will help to increase resource reliance in Organizations. Moreover, it will assist firms in increasing productivity, increasing employee loyalty and morale, and making organizational operations run more smoothly. The study provides empirical evidence for policy formulation in the area of administration of justice, a contribution to the existing literature on the influence of organization resources and organizational performance, and an affirmation of the resource-based theory.